Feeding behavior comparison of soybean aphid (Hemiptera: Aphididae) biotypes on different soybean genotypes - Chandran, Predeesh; Reese, John C.; Khan, Shah Alam; Wang, Dechun; Schapaugh, William T., Jr.; Campbell, Leslie R. (My University, 2014)
Soybean aphids have become a serious pest of soybean, Glycine max L. (Merrill), since they were first detected in North America in 2000. Three soybean aphid biotypes have been documented in the United States in the last 10 yr, but few studies have been done on their feeding behavior in the United States The Electrical Penetration Graph is a convenient and successful tool to study the feeding behavior of piercing and sucking insects. This is the first attempt to study the feeding behavior differences between biotype 1 and biotype 2 on soybean genotypes using the Electrical Penetration Graph technique, and includes both resistant and susceptible soybean genotypes from Kansas and Michigan. The experiments were run for 9 h each for each genotype with a total of eight channels at a time. Results indicated that aphids feeding on susceptible genotypes had a significantly greater duration of sieve element phase than when feeding on resistant genotypes. Furthermore, the time taken to reach the first sieve element phase in resistant genotypes was significantly greater than in susceptible genotypes. Most of the aphids reached sieve element phase (>90%) in susceptible genotypes, but only a few (<30%) reached sieve element phase in resistant genotypes during the 9-h recording period; however, we found no differences in any other probing phases between resistant and susceptible genotypes except the number of potential drops in biotype 2. Thus, the resistance was largely associated with phloem tissues. Therefore, some biochemical, physical, or morphological factors could affect stylet penetration of aphids.
Citation: Chandran, Predeesh, John C. Reese, Shah Alam Khan, Dechun Wang, William Schapaugh, and Leslie R. Campbell. 2013. “Feeding Behavior Comparison of Soybean Aphid (Hemiptera: Aphididae) Biotypes on Different Soybean Genotypes.” Journal of Economic Entomology 106 (5): 2234–40. https://doi.org/10.1603/EC13126.
Keywords: EPG; Aphid biotype; Soybean Genotype; Feeding behavior